Analisis Tingkat Kepuasan Konsumen Terhadap Kualitas Produk dan Layanan Pada Kedai Kadieu Di Kabupaten Badung Bali - Musmi, Nurhayati; Wiranatha, Anak Agung Putu Agung Suryawan; Yoga, I Wayan Gede Sedana (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
As a culinary company that has recently faced very tight competition, Kedai Kadieu has to decide how best to face its competitors. The aim of this research is to identify product and service quality attributes that are considered important by consumers, to find out the main priority attributes for improvement for consumer satisfaction. Apart from that, and knowing the level of consumer satisfaction with these attributes. The methods used are the IPA method and the CSI method. The technique for collecting data is using purposive sampling. The results of the research show that the attributes of drink consistency for each serving and suitability of food prices to portions and food quality are product quality attributes that are considered very important by Kedai Kadieu customers, the quality of service that is considered very important includes the cleanlines and tidines of the place, the patient attributes and calmness of employees in serving consumers, and the customer comfort attributes while at Kedai Kadieu. The priority attributes for improvement in product quality are the taste of food and consistency of food at each serving, while in service quality is speed in service and presentation. The CSI results show that all product and service attributes are considered very important by consumers with an MIS value greater than 4.20 and a consumer satisfaction level value of 84% in the very satisfied product quality category and 83.1% with a very satisfied category on service quality.